Protein and Ribonucleic Acid Synthesis During the Diploid Life Cycle of Allomyces arbuscula - Burke, Daniel J. (1972)
The diploid life cycle of Allomyces arbuscula may be divided into four parts: spore induction, germination, vegetative growth, and mitosporangium formation. Spore induction, germination, and mitosporangium formation are insensitive to inhibition of actinomycin D, probably indicating that stable, pre-existing messenger ribonucleic acid (RNA) is responsible for these developmental events. Protein synthesis is necessary during the entire life cycle except for cyst formation. A system for obtaining synchronous germination of mitospores is described. During germination there is a characteristic increase in the rate of synthesis of RNA and protein although none of the other morphogenetic changes occurring during the life cycle are necessarily accompanied by an appreciable change in the rate of macromolecular synthesis.